How knowledge, awareness and perceptions of pesticide residue risks in fruits and vegetables, influence purchase decisions across Malaysian communities - How, Vivien; Omar, Ain Najwa Delaila; Abdullah, Rozaini; Ho, Yu Bin (Springer Nature, 2024)
Understanding consumer perceptions and behaviours toward pesticide residues in food is vital for food safety and public health. This study examines the knowledge, awareness, and perceptions of 303 participants from rural, suburban, and urban Malaysian communities regarding pesticide residue risks in their food purchases, particularly fruits and vegetables. Participants completed adapted questionnaires via Google Forms or in-person interviews, covering sociodemographic information, food purchasing habits, and levels of knowledge, awareness, and perception of pesticide residues. Results indicate that urban communities have the highest knowledge about pesticide residues, followed by rural and suburban areas. Awareness levels are even across all community types, with rural areas slightly higher. Urban participants also show the highest perception levels, followed by rural and suburban communities. Rural communities demonstrate a strong positive correlation between knowledge and perception, while suburban areas show a moderately positive correlation. Urban communities exhibit significant correlations between knowledge awareness and perception, with a weaker relationship with awareness. These findings highlight the interplay between community settings and consumer behaviour in purchasing fruits and vegetables. The study emphasises the need for tailored educational and policy interventions to address the varying levels of knowledge and concerns about pesticide residues across different Malaysian communities. © The Author(s) 2024.